2004
DOI: 10.1038/sj.bjc.6601454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of frequent Bcl-2 expression on better prognosis in renal cell carcinoma patients

Abstract: Previously, we reported that Bcl-2 was frequently expressed in renal cell carcinoma (RCC) specimens, but p53 mutation was a rare event. However, it was unclear whether Bcl-2 positivity was associated with the clinicopathological characteristics and prognosis in RCC. Therefore, we investigated the expression of Bcl-2 protein and its roles in 101 RCC specimens. In addition, the proliferation index (PI), apoptotic index (AI), caspase-3 and p53 expression were examined. The immunohistochemical method was applied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 24 publications
(31 reference statements)
5
36
0
2
Order By: Relevance
“…Visualisation of stained blots was performed with the ECL Western Blotting Detection system (Amersham) according to the manufacturer's instructions. Immunohistochemical staining was performed using the avidin -biotin peroxidase complex method with 5 mm cryostat sections from frozen tissue as described earlier (Itoi et al, 2004). We classified the immunoreactivity as positive or negative.…”
Section: Immunoblotting and Immunohistochemistrymentioning
confidence: 99%
“…Visualisation of stained blots was performed with the ECL Western Blotting Detection system (Amersham) according to the manufacturer's instructions. Immunohistochemical staining was performed using the avidin -biotin peroxidase complex method with 5 mm cryostat sections from frozen tissue as described earlier (Itoi et al, 2004). We classified the immunoreactivity as positive or negative.…”
Section: Immunoblotting and Immunohistochemistrymentioning
confidence: 99%
“…Furthermore, the frequent expression of Bcl-2 and the absence of p53 gene alterations were found in these RCC specimens (Tomita et al, 1996b). Most recently, we reported the relationship between Bcl-2 expression and good prognosis in RCC patients and demonstrated a significant difference in survival between Bcl-2-positive and -negative patients without metastasis (Itoi et al, 2004). Nevertheless, the role of Bcl-2 appeared to be equivocal in patients with metastatic disease.…”
mentioning
confidence: 92%
“…The following primary monoclonal antibodies were used -anti-Bcl-2 clone 124 (1/100 dilution, Dako, Glostrup, Denmark), anti-Fas clone UB-2 (1/100 dilution, Medical Bioscience Laboratory, Nagoya, Japan) and anti-human Ki-67 antigen clone MIB-1 (1/100 dilution, Dako). The specificity of each antibody to Bcl-2 and Fas had been confirmed previously (Itoi et al, 2004;Yamana et al, 2005). Negative controls were prepared by omission of the primary monoclonal antibodies.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Published results on the association of p53 with survival have been controversial, some studies suggesting positive p53 associating with poor survival (Shvarts et al 2005, Zigeuner et al 2004, Uchida et al 2002, Haitel et al 2000, while others have observed no association (Itoi et al 2004, Olumi et al 2001, Rioux-Leclercq et al 2000, Hofmockel et al 1996. In the study of Phuoc et al (2007), p53 was significantly associated with survival in univariate analysis, but the association was not independent.…”
Section: P53 Biomarker Of Cell Cycle Pointmentioning
confidence: 99%
“…An association between Ki-67 and high T-stage and metastases development have been observed (Kankuri et al 2006, Dudderidge et al 2005, Rioux-Leclercq et al 2000, indicating that Ki-67 is a marker for aggressive disease in RCC with an increased risk of early metastases development. Ki-67 has been reported to independently predict survival following nephrectomy in many studies (Dudderidge et al 2005, Bui et al 2004, Itoi et al 2004, Rioux-Leclercq et al 2000, Aaltomaa et al 1997. Ki-67 has been observed to increase in sarcomatoid change (Kanamaru et al 1999), indicating different protein expression profiles in different entities according to the Heidelberg classification.…”
Section: Ki-67 Proliferation Markermentioning
confidence: 99%